Complex and System Thinking in Physical Education and Physical Activity Promotion - Carlos Mario Arango-Paternina; Willinton Javier Watts-Fernández; Ross Brownson (Universidad de Antioquia, 2022)
Here we explore the advantages and limitations of adopting and implementing complex and systemic thinking in physical education and physical activity promotion. To this end, we have revisited contributions from the critical theory and complex and systemic thinking. From the intersection of these fields of knowledge and understanding physical education and the promotion of physical activity as complex systems, we seek to adopt an integrative and relational stance to advance the disciplines of human body movement. We have also discussed the advantages and challenges of applying approach and suggest examples of systemic intervention. Finally, we analyze and describe the limitations and real-world barriers to its application.